Differing clinical features between Japanese and Caucasian patients with myelodysplastic syndromes: Analysis from the International Working Group for Prognosis of MDS - Miyazaki, Yasushi; Tuechler, Heinz; Sanz, Guillermo; Schanz, Julie; Garcia-Manero, Guillermo; Solé, Francesc; Bennett, John M; Bowen, David; Fenaux, Pierre; Dreyfus, Francois; Kantarjian, Hagop; Kuendgen, Andrea; et al. (Leukemia research, 2018)
Clinical features of myelodysplastic syndromes (MDS) could be influenced by many factors, such as disease intrinsic factors (e.g., morphologic, cytogenetic, molecular), extrinsic factors (e.g, management, environment), and ethnicity. Several previous studies have suggested such differences between Asian and European/USA countries. In this study, to elucidate potential differences in primary untreated MDS between Japanese (JPN) and Caucasians (CAUC), we analyzed the data from a large international database collected by the International Working Group for Prognosis of MDS (300 and 5838 patients, respectively). JPN MDS were significantly younger with more severe cytopenias, and cytogenetic differences: less del(5q) and more +1/+1q, -1/del(1p), der(1;7), -9/del(9q), del(16q), and del(20q). Although differences in time to acute myeloid leukemia transformation did not occur, a significantly better survival in JPN was demonstrated, even after the adjustment for age and FAB subtypes, especially in lower, but not in higher prognostic risk categories. Certain clinical factors (cytopenias, blast percentage, cytogenetic risk) had different impact on survival and time to transformation to leukemia between the two groups. Although possible confounding events (e.g., environment, diet, and access to care) could not be excluded, our results indicated the existence of clinically relevant ethnic differences regarding survival in MDS between JPN and CAUC patients. The good performance of the IPSS-R in both CAUC and JP patients underlines that its common risk model is adequate for CAUC and JP.
Keywords: Myelodysplastic syndromes; senioři; Aged; Male; Retrospective Studies; lidé; myelodysplastické syndromy; přežití bez známek nemoci; Humans; míra přežití; Disease-Free Survival; běloši; retrospektivní studie; Clinical features; Survival Rate; White People; Karyotype; Myelodysplastic Syndromes; mužské pohlaví; Asian People; Ethnicity; Survival; Asijci; ženské pohlaví; Female